Fostering methodological advances and technical capacity building. (30th September 2020) - Grant, I; Plass, D; von der Lippe, E; Lesnik, T; Idavain, J
Abstract: Countries all over the world, and especially in Europe, are increasingly using the burden of disease approach to assess the health status of populations and to identify the main drivers of ill health. Thus, there is an increasing need for equitable capacity building on the one hand (including an improved understanding of the complex methods behind global and national burden estimates), and harmonization of methods on the other hand to keep the results comparable. Furthermore, involved researchers also strive for a platform to exchange experiences and foster collaboration. To address the current challenges in burden of disease research, our COST Action CA18218-European Burden of Disease Network will build strongly on the COST mechanisms, such as short-term scientific missions and training schools to foster and increase capacity building activities across Europe. Our Action will also serve as a technical platform where knowledge and expertise can be shared among experienced and less experienced researchers. Collaboratively, the technical platform will provide unique opportunities for developing a joint research agenda in the domain of burden of disease, for fostering methodological developments, and for developing new collaborative research. With this presentation, we aim to show how the COST Action is fostering methodological advances and technical capacity building, focusing on 1) the role and aim of short-term scientific missions including real case examples; 2) the concept and structure of the Action's training schools; and 3) examples of specific methodological activities underway as part of the Action. The session will conclude with an interaction with the audience during which the needs and expectations of the attendees will be elicited.